Vivax malaria in children: clinical features and response to chloroquine. - Carmona Fonseca, Jaime; Uscátegui, Rosa M.; Correa, Adriana María (Colombia Medica, 2008)
Introduction: In Colombia is not very common to find updated information about vivax malaria in children. Aims: Describe the clinical and paraclinical disease picture and evaluate the standard dose of chloroquine effectiveness as a cure for the acute attack of vivax malaria in children between 4 and 10 years old. Methods: Experimental design, balanced, not blind, 82 patients and habitants in El Bagre and Turbo, Colombia. Follow-up: 30 days. Results: Symptoms-signs agreed with the known. There were found 62% long-term malnutrition, 53% anemia, low retinol (19 μg/dl), normal leukocyte count, normal liver tests and normal creatinine coefficient. After 25-28 day of treatment, all alterations had disappeared on children except malnutrition. According with the analysis techniques, the chloroquine late failure proportion was: by the intention to treat 2.4% (0 to 24%), by the protocol 2.6% (0 to 25%), and in the worst-case scenario 7.3% (0 to 29%). Conclusion: The clinical and paraclinical depict was similar than adults. Malaria, was the main responsible for clinics and paraclinical alterations. Chloroquine, without primaquine, proved highly effective for the acute attack of vivax malaria in children and should be retained as the first therapeutic option.